Evaluation of Bismuth based inorganic sorptive media for Simultaneous removal of nitrate, fluoride and arsenic From ground water for drinking purpose - Ranjan, Manish (IIT(BHU) Varanasi, 2020)
Abstract is available in content
This thesis is uploaded by IIT BHU
Keywords: inorganic sorptive media; removal of nitrate; fluoride and arsenic; water for drinking purpose